2017
DOI: 10.1016/j.ijscr.2017.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Small bowel lymphangioma causing ileo-ileal intussusception in adults

Abstract: HighlightsLymphangioma is a benign tumor which is rarely found in gastrointestinal tract.They are mainly due to malformations of the lymphatic system.Colonoscopy and endoscopic ultrasonography are frequently used to diagnose lymphangiomas of the small bowel.The clinical presentation of abdominal lymphangioma is diverse, however typically patients are asymptomatic or have nonspecific symptoms, signs and symptoms include intermittent, cramping abdominal pain, diarrhea, fullness, abdominal mass.GI bleed occurs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…There have been several case reports on the patients with small intestinal lymphangioma causing intussusception in adults [ 1 , 3 , 4 , 6 ]. In all these reports, the patients presented with abdominal pain with or without nausea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been several case reports on the patients with small intestinal lymphangioma causing intussusception in adults [ 1 , 3 , 4 , 6 ]. In all these reports, the patients presented with abdominal pain with or without nausea.…”
Section: Discussionmentioning
confidence: 99%
“…Adult intussusception is rare, with 90% of the cases caused by a gastrointestinal pathology, including adhesion or tumors [ 1 , 2 ]. Lymphangiomas are benign tumors resulting from congenital lymphatic system malformation [ 3 ], generally located in the head and neck regions or the axilla. The gastrointestinal lymphangioma accounts for only 1% of all [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ninety five percent of lymphangiomas are located in the head and neck [1,2]. Abdominal lymphangioma is rare (1-5%) and most cases (80%) are related to the small bowel mesentery [3]. However, it may occur in any part of the gastrointestinal tract and may be detected in the retroperitoneal space, spleen, liver, gall bladder, adrenal glands, pancreas and the lesser omentum.…”
Section: Introductionmentioning
confidence: 99%
“…Studies also reported simultaneous occurrence of lymphangioma in the abdominal cavity and mediastinum [4]. Clinical presentation can be asymptomatic, chronic with non-specific symptoms associated with the mass effect (lumbar pain, vomiting, bowel movement disorder) or acute symptoms related to intestinal obstruction [3], infection of the cystic mass, or bleeding from/ into the tumor [5]. Cases of gastrointestinal bleeding were also reported [6,7].…”
Section: Introductionmentioning
confidence: 99%